A Brief Review of Phenolic Antioxidant and their Biological Activity - Shakir, Raied Mustafa; Jasim, Husam Salman; Saoud , Shaimaa Abed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Antioxidant compounds are considered essential materials because they prevent or reduce free radical side chain reactions, which cause much damage. It is widely acknowledged that these damages are a major contributing factor to numerous diseases. Phenolic antioxidants are considered one of the most important antioxidant species. There is ample evidence that the antioxidant substances found in fruits and vegetables can prevent various diseases such as cancer, heart disease, diabetes, and cataracts. The food and pharmaceutical industries also make extensive use of it. Additionally, quite several phenolic medicinal compounds for anticancer, anti-inflammatory, anti-necrotic, hepato-protective, and neuroprotective purposes possess antioxidant abilities. The synthetic phenolic compounds exhibited remarkable antioxidant capacity in addition to various biological activities. These facts prompted the researchers to focus on newly synthesized phenolic compound derivatives and explore their biological activities, particularly those containing heterocyclics in their molecular structures. The biological activities of heterocyclic compounds are widely recognized.